Laparoscopic treatment of postoperative hernias with intraperitoneal mesh Parietex composite in oncological patients – initial results - Murawa, Dawid; Połom, Karol; Spychała, Arkadiusz; Nowaczyk, Piotr; Niziołek, Aleksander (Contemporary Oncology/Współczesna Onkologia, 2009)
Introduction: The frequency of hernias after large abdominal surgery is still a huge problem. It affects 2–11% of patients. In case of oncological surgery the risk is even higher. It is not estimated how to treat postoperative abdominal hernias. The open question is about technique and about used materials. Last years laparoscopic surgery plays a role in abdominal postoperative hernias repair. Thanks this technique less complications are seen, and faster patient is able to leave the hospital. Aim of the study: Presentation of laparoscopic technique and initial results of laparoscopic treatment in postoperative abdominal hernia repair in oncological patients. Material and methods: From January to May 2008, 4 patients were operated on laparoscopic technique, because of postoperative abdominal hernia. All patients were previously operated because of colon cancer (3 patients) or gastric cancer (1 patient), with adjuvant chemotherapy. Comorbidities were (4 patients – hypertension, 2 patients – diabetes). All hernias were situated in the middle line, and the sizes were: 18 × 21 cm, 8 × 6 cm, 7 × 6 cm, 7 × 5 cm. Results: Hernia repair was performed by using intraperitoneal mesh – Parietex Composite sized 25 × 20 and 15 × 10. After the mesh was positioned intracorporeally, by 4 sutures and Protack to secure the mesh. There were no postoperative complications. During a follow up time range 9-13 months no recurrences were observed. Conclusions: Laparoscopic treatment of postoperative hernias is an effective and safe procedure in oncological patients. Analysis of early and long-term results require larger group of patients. In Poland the main problem, despite all positives is a cost of the mesh.